Generating social and environmental awareness among computer science students - Díaz, Francisco Javier
Since 2007, the Computer Science School of the National University of La Plata (Buenos Aires, Argentina) has been involved in extension projects related to social and environmental issues, where students of the Computer Science degrees are called upon to participate and collaborate actively. At the beginning, we started working on the project called Reduciendo la Brecha Digital en Sectores Desfavorecidos de la Sociedad (Reducing the Digital Divide in Underprivileged Sectors of Society), where students and teachers went voluntarily to diners in order to teach Computer Science to children and adolescents of limited resources. We approach this from two teaching perspectives: training the students in basic PC operation concepts and teaching them to use a computer as a learning tool for other disciplines. Because the diners had no computing resources, the training took place in cybercafes near the neighborhood. In 2009, another project came to be as a result of a growing concern about the destination of the computing equipment that was no longer in use. Normally, this is discarded and generates electronic waste. Thus, a group was formed to work on the reuse, restoration and recuperation of Waste Electrical and Electronic Equipment (WEEE). In 2010, both projects were united, allowing for the donation of the restored computing equipment to the training venues, solving the problem of lack of equipment in the diners. Not only are the institutions that were excluded from ICTs given adequate computing information, but also the necessary equipment and resources. Voluntary workers, all students, can assume the role they prefer with the wide range of activities offered from different disciplines, such as computer science, engineering and education. Among the most important activities are taking apart disused equipment, selecting usable components, putting an equipped PC together, and installing and selecting free software computer applications, both offimatic and educational. The students an also take part in the development of the classes, dictate them, make curricular lists, and set up and maintain an internal wiki with material for the classes and data on the performance of each student. This article consists of presenting these initiatives, passed in successive calls by the Presidency of the UNLP and the National Ministry of Education, which allowed for the voluntary participation of over 50 computer science students. Project characteristics, motivations and results, both in the audience and among the participating computer science students, will be described in this article. It is quite gratifying to be given the opportunity to strengthen the bond between the school and underprivileged social sectors in terms of technology, while achieving a more profound ethical and supportive formation for computer science students with a social commitment and environmental awareness, who understand how computer science can be applied to the cause of reducing the digital divide that exists in the most underprivileged sectors of society and collaborating in environmental matters.